Chemsex and its repercussions on the health of men who have sex with men (MSM) - de Sousa, Alvaro Francisco Lopes (2023)
Funding Information: Braziliam National Research Council – CNPq. Process: 159908/2019-1. Publisher Copyright: © 2023, Associacao Brasilerira de Enfermagem. All rights reserved.